2016
DOI: 10.1097/inf.0000000000000988
|View full text |Cite
|
Sign up to set email alerts
|

Influenza-like Illness in Households with Children of Preschool Age

Abstract: ILI in households with preschool children has a considerable societal impact. Risk-mitigating initiatives seem justified for day-care attendees, mothers, people with chronic respiratory conditions, and children with developmental disabilities. Children attending day care for >2 years acquire some protection to ILI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…This result seems, at first, particularly surprising, when thinking about the significant role children play in the spread of ILI. Mughini et al [ 34 ] performed a survey analysis on ILI in families with children younger than 4 years, results showed that parents of ILI-affected children had a concurrent 4-fold higher ILI risk. The small statistical difference in children population between boroughs with low and high ILI rates (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This result seems, at first, particularly surprising, when thinking about the significant role children play in the spread of ILI. Mughini et al [ 34 ] performed a survey analysis on ILI in families with children younger than 4 years, results showed that parents of ILI-affected children had a concurrent 4-fold higher ILI risk. The small statistical difference in children population between boroughs with low and high ILI rates (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we were not able to adjust for exposure to all possible sources of infection during the study. For example, people with young children may be at higher risk for ILI/ARI episodes (29), but we did not have information on household composition. However, adjustment for age may have partly accounted for this.…”
Section: Discussionmentioning
confidence: 99%
“…The societal burden of AGE was expressed as incidence, episodes/person-year (calculated as [365/28] × [4-weekly incidence proportion]) 3 5 32 , medical care (general practitioner [GP] visits and hospitalizations), work and DCC days missed.…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire was developed by expanding those used in previous population-based studies in the Netherlands 3 28 30 31 32 . Questions covered the prior four weeks and focused on household characteristics, DCC attendance, chronic diseases, medications, symptoms, medical care, absenteeism from work and from DCC, occupation, contact with animals, leisure activities, and eating habits ( Supplementary Table S1 ).…”
Section: Methodsmentioning
confidence: 99%